Metamorfoses de Júpiter nos Amores de Ovídio: Jupiter’s metamorphosis in Ovid’s Amores - Duque, Guilherme Horst (Rónai – Revista de Estudos Clássicos e Tradutórios, 2016)
Partindo de observações de John T. Davis, em Fictus Adulter: Poet as an Actor in the Amores (1989), o presente trabalho se dedica à análise das figurações de Júpiter nos Amores de Ovídio com o objetivo de demonstrar sua influência na construção do amans elegíaco ovidiano. Para Davis, o deus, que em múltiplas ocasiões é referido ao longo das elegias como adulter, ocupa a posição de modelo de amante bem-sucedido para Ovídio, tendo sua capacidade de se transformar para alcançar seus propósitos enfatizada. Abstract Based on the observations of John T. Davis in Fictus Adulter: Poet as an actor in the Amores (1989), this paper aims to analyze Jupiter’s depictions in the Amores of Ovid in order to demonstrate its influence on the representations of the Ovidian elegiac amans. Davis argues that in multiple occasions the god if referred to in the elegies as adulter, filling the role-model of the successful lover to Ovid, with emphasis on his ability of transformation to achieve his goals. Keywords: Roman love elegy; Ovid; Amores; metamorphosis; Jupiter.